2020
DOI: 10.1029/2020gl088898
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Ice Under Arctic Pack Ice in Winter

Abstract: The formation of platelet ice is well known to occur under Antarctic sea ice, where subice platelet layers form from supercooled ice shelf water. In the Arctic, however, platelet ice formation has not been extensively observed, and its formation and morphology currently remain enigmatic. Here, we present the first comprehensive, long‐term in situ observations of a decimeter thick subice platelet layer under free‐drifting pack ice of the Central Arctic in winter. Observations carried out with a remotely operate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…First results with a focus on snow and sea ice conditions have been published, for example, on the history of the ice drift prior to the MOSAiC expedition , on the ice conditions from satellite observation along the drift track in previous years (Krumpen et al, 2021), on the representativeness of the selected ice floe (Belter et al, 2021), on the linkages to the general atmospheric circulation (Dethloff et al, 2021), on sea ice RS methods (Munoz-Martin et al, 2020;Stroeve et al, 2020;Semmling et al, 2021), and on the platelet ice accumulation in winter (Katlein et al, 2020).…”
Section: Methods and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…First results with a focus on snow and sea ice conditions have been published, for example, on the history of the ice drift prior to the MOSAiC expedition , on the ice conditions from satellite observation along the drift track in previous years (Krumpen et al, 2021), on the representativeness of the selected ice floe (Belter et al, 2021), on the linkages to the general atmospheric circulation (Dethloff et al, 2021), on sea ice RS methods (Munoz-Martin et al, 2020;Stroeve et al, 2020;Semmling et al, 2021), and on the platelet ice accumulation in winter (Katlein et al, 2020).…”
Section: Methods and Approachmentioning
confidence: 99%
“…The novel observation of platelet ice under winter sea ice in the Arctic showed that platelet ice contributed to bottom ice growth during winter (Katlein et al, 2020). Over time, the ice pack became strongly deformed.…”
Section: Sea Ice and Snow Mass Balancementioning
confidence: 99%
“…Supercooled water, that is, water with a temperature below a reference freezing point temperature, has been observed in the polar oceans of the Arctic (e.g., Drucker et al., 2003; Katlein et al., 2020; Skogseth et al., 2009) and Antarctic (e.g., Brett et al., 2020; Countryman, 1970; Lewis & Perkin, 1986). Seawater may be supercooled relative to the local freezing point, making it “in situ” supercooled (Ushio & Wakatsuchi, 1993), or the surface ocean freezing point, making it “potentially” supercooled (Shcherbina et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Potential supercooling could also result from downward mixing of frazil ice by strong winds (Matsumura & Ohshima, 2015). Additionally, supercooling is observed in the Arctic under a closed sea‐ice cover and calm conditions (Katlein et al., 2020; Peterson, 2018) and is potentially related to the rejection of cold brine from sea ice. Prior to the present study, there had been no evidence of widespread sea ice‐induced supercooling or the occurrence of supercooled waters away from the continental shelf in the Southern Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Subice platelet layers can be separated from frazil ice in such way that the geometric size of the platelet ice crystals is on the order of 1-10 cm. Frazil ice describes the crystal habit resulting from the initial stages of sea ice growth, when small disk and needle-like crystals smaller than 1 cm appear suspended in the upper water column or at the ocean surface (Hoppmann et al, 2020;Weeks & Ackley, 1986;Zubov, 1963). Subice platelet layers exhibit a rather random orientation of crystal axes.…”
Section: Introductionmentioning
confidence: 99%